Flexural behavior of continuous beams consisting of normal concrete and SIFCON under static and repeated loads. Issue 1 (June 2020) - Abeer, S Z; Dawood, M B; Ghalib, M H
Abstract: In this paper Slurry Infiltrated Fiber Concrete (SIFCON) has been used at plastic hinge locations to fix the ductility problem of continuous reinforced concrete beams. The use of SIFCON in compression parts of plastic hinge zones for continuous beam has been experimentally studied under both static and repeated loads. Six continuous beams with full scale have been tested; two with normal concrete totally and four with SIFCON at compression parts of plastic hinge locations. Three fraction volumes of fibers (Vf) % have been considered, 7%, 9% and 11%. Also, the influence of using SIFCON parts on redistribution of bending moment for continuous beams is investigated. It was noticed that, in all the reinforcement concrete beams, the using of SIFCON increased the capacity and ductility of the samples at same time. The improvement in the flexural capacity, the toughness and the moment redistribution for continuous beams could reach as high as 20%, 20% and 104% respectively. In addition, it was found that the reduction in flexural strength of composite continuous beam when it exposures to repeated loads was about 0.6% in comparison with that under static loads.